Students’ Perceptions Of Lecturers’ Roles In Online Classes At English Education Study Program Of Muhammadiyah University Of Bengkulu - Rinti Safetri; Kiagus Baluqiah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this study is to determine students’ perceptions of lecturers’ roles in online clasroom in the second, fourth and sixth semester students of English Education Program of Muhammadiyah University of Bengkulu. The researchers used the qualitative research method. The qualitative research was used to obtain more in-depth information on the students perceptions of lecturers’ roles in online classes. The research subjects were all the second, fourth and sixth semester students of English Education Study Program at Muhammadiyah University of Bengkulu. There were 107 students in total. The researchers used the questionnaire as the instrument in this study. The questionnaire was adopted from Huang (2017). The findings indicated that the perception of the second semester students was positive response with the criteria good. The fourth semester students’ perception is mostly positive response with the criteria very good, while many of the sixth semester students chose positive responses with the criteria very good. It means that the findings can guarantee that the students of English study study program of Muhammadiyah University of Bengkulu averagely have a good perception of the lecturers’ role in online classes. Keywords : Students’ Perceptions, Lecturers’ Roles, Online Classes